(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Introduction: The problem of perception of insufficient breast milk, anxiety, and concerns about breastfeeding practices are closely related to the mother's psychological condition, so a solution must be found. This study focuses on mothers with problems regarding breastfeeding, such as perceived insufficient milk supply, anxiety, and fear of breastfeeding. Methods: This study is a quasi-experimental pre-post-test study on 30 breastfeeding mothers. Participants were searched online through social media and Facebook and given a questionnaire regarding screening for breastfeeding problems. Each respondent received NLP method therapy with sub modality techniques and anchoring as needed starting 1-2 hours and evaluated on days three and six after therapy. The evaluation was carried out immediately after therapy, three days after therapy, and six days after therapy. Results: The results of this study estimated that neurolinguistic programming for six weeks reduced feelings of perceived insufficient milk supply (P < 0.001). These results also show that neurolinguistic programming has a very large effect (Cohen, 1988) on reducing feelings of perceived insufficient milk supply (1.00). During the six weeks of implementing neuro linguistic programming, respondents' feelings about perceived insufficient milk supply of respondents. PIM experience also decreases over time. PIMS feelings will decrease 0.17 to 0.57 points shortly after neurolinguistic programming up to 6 days later. Conclusion: Perceived insufficient milk supply caused by maternal stress factors, maternal malnutrition, and traditional beliefs about food and eating can be treated with neurolinguistic programming because NLP with communication and persuasive concepts to change behaviour can increase endorphin production, which further increases the release of the hormone oxytocin so that breast milk production will not decrease and reduce the prevalence of early weaning in the first six months. We suggest that this method be implemented in every health facility by a certified health worker in the field of NLP.